PELATIHAN VIDEO EDITING DI SMP IT MADANI - Ahmad Zamsuri; Wenni Syafitri; Febrizal As-Syam (Universitas Lancang Kuning, 2018)
SMP IT Madani is formed from LAZ Swadaya Ummah Riau Province. SMP IT Madani is a free school. The vision promoted by SMP IT Madani is as follows: